2020
DOI: 10.3390/medsci8030029
|View full text |Cite
|
Sign up to set email alerts
|

Postpartum Follow-Up of Women Who Developed Subclinical Hypothyroidism during Pregnancy

Abstract: There is inconsistency in the literature regarding the management of women diagnosed with subclinical hypothyroidism (SCH) during pregnancy in the postpartum period. The purpose of our study was to assess the need for continuation of levothyroxine (LT4) treatment after delivery. We conducted a retrospective cohort study of 114 women with new-onset SCH during pregnancy and at 1-year follow-up postpartum. Criteria for continuation of LT4 after delivery were breastfeeding, thyrotropin (TSH) levels at diagnosis &g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 22 publications
1
3
0
Order By: Relevance
“…This dose, larger more than the 50 µg cut-off suggested by ATA guidelines (3), might be explained by the inclusion of OH patients with higher peri-conception TSH levels and greater substitution need during pregnancy. In our long-term hypothyroid patients, like in the study by Li et al (10), the LT4 treatment was initiated at an earlier gestational age, demonstrating the lack of adaptation of these patients to the metabolic stress of the pregnancy.…”
Section: Discussionsupporting
confidence: 58%
See 3 more Smart Citations
“…This dose, larger more than the 50 µg cut-off suggested by ATA guidelines (3), might be explained by the inclusion of OH patients with higher peri-conception TSH levels and greater substitution need during pregnancy. In our long-term hypothyroid patients, like in the study by Li et al (10), the LT4 treatment was initiated at an earlier gestational age, demonstrating the lack of adaptation of these patients to the metabolic stress of the pregnancy.…”
Section: Discussionsupporting
confidence: 58%
“…We show in our study that the TSH level at treatment initiation and the maximal LT4 dose during pregnancy are predictive of persistent hypothyroidism. Previous studies have found associations between long-term hypothyroidism and TSH >5 mU/l at diagnosis (6,7,10), LT4 dose at the end of pregnancy (7), TPOAb (6)(7)(8) or TgAb (8) positivity at diagnosis and at 6 weeks post-partum follow-up (8), gestational age at treatment initiation (8), multiparity (10) or maternal age (7). TSH was significantly higher at LT4 initiation in patients who were long-term hypothyroid in our study and a TSH level >3.8 mU/l was predictive of this evolution.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations